Efficacy of Topical Silymarin and Intradermal Injection of Tranexamic Acid in the Treatment of Melasma: A Comparative Study - Syed Bilal Ahmed, Sajida Jabeen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Melasma is a skin disorder that mostly effect females in reproductive age. Modern treatment techniques are needed to address these issues. Objective: The aim of this study was to explore the efficacy of topical silymarin and intradermal injection of tranexamic acid in the treatment of melasma. Material and Method: The current randomized control trial study was carried out at PGMIQ/ BMC Hospital Quetta from January 2023 to June 2023 after taking approval from the ethical board of the institute. A total of 76 individuals of both gender and different age groups (15-45 years) presented with melasma to the dermatology department were included. The study participants were randomly divided equally in to two groups of 38 individuals each. Group A was administered silymarin cream twice a day for 12 weeks, whereas Group B got weekly intradermal injections of tranexamic acid. The modified Melasma Area and Severity Index score was determined at the beginning of therapy, at each follow-up appointment, and at the end of treatment. At the end of three months of therapy, efficacy was evaluated, and a mMASI score reduction of more than 50% from the baseline considered effective. To analyze the data, SPSS version 24.0 was used. To investigate effect modifiers, data stratification was carried out for age, gender, lesion location, severity, and disease duration. The Chi Square test was used to compare the effectiveness of the two groups and post-stratification, with a P-value of ≤0.05 being considered statistically significant. Results: A total of 76 individuals participated in this study out of which 58(76.3%) were females and 18(23.6%) were male. Participants in Group A had a mean mMASI score of 11.91±4.95 at baseline, while those in Group B had a mean score of 14.36±4.93 (the p-value=0.038). Patients in Group A had a mean mMASI score of 7.33±3.74 at the end of therapy, while those in Group B had a mean score of 6.67±2.89 (p-value=0.41). The mean change in the mMASI score was 8.58±3.11 in Group B and 4.6±1.95 in Group A. The p-value was less than 0.05, indicating that the difference was significantly different. Our study’s findings revealed that 17 (44.7%) of the 38 participants in Group A experienced efficacy and 21(55.2%) did not. However, 26 (68.4%) of the 38 participants in Group B confirmed that the therapy was effective. The difference was considered statistically significant, with a P-value of 0.03. There was no statistically significant variation in the effectiveness stratification according to age and gender, (p value was greater than 0.05). Conclusion: Our study concluded that for the treatment of melasma topical silymarin is not statistically as effective as intradermal injection of tranexamic acid. Keywords: Efficacy; Topical; Silymarin; Intradermal injection; Tranexamic acid; Melasma